Genômica comparativa em gramíneas. - Bervald, Clauber Mateus Priebe (2009)
The use of sequences of DNA has been the base of comparative genomics for evolutionary studies. The transfer of information from model species to agricultural species has been revolutionizing the molecular genetics and strategies of crop improvement. The combination of classic methods of genetics and breeding with molecular technologies of genomic analysis opens a new perspective for the increase of the understanding of the genetic basis and the acceleration of breeding programs. Bioinformatics is becoming a tool that will be an essential part of the plant scientific research contributing to this challenge, and allowing inferences of function, structure and evolution of genes and genomes, search of markers, primers design, among other possibilities. In this sense, three studies of comparative genomics in grasses were accomplished, using bioinformatics tools. In the first work, the objective was to analyze the microsatellite abundance in genome fractions of 13 species of the genus Oryza, describing the rates, frequencies and pattern of distribution of the different microsatellites. The microsatellite frequency varies inversely proportional to the size of the genome of the specie of the genus Oryza. The A genome species presented the highest occurrences and frequencies for all types and total microsatellites. The trimers composed by cytosines and guanines presented the percentile largest of occurrence among the species, without direct relationship with the GC content of the species. In the second work, the promoter region of 1,000 bases pairs of the genes OsNramp of Oryza sativa subsp japonica cv. Nipponbare was investigated as for the abundance of cis-acting elements. The sequences were analyzed using the software Signal Scan Search of the website Plant Cis-acting Regulatory DNA Elements (PLACE) to the identification of different cis-acting elements present in each one of the promoter regions. Were detected 170 different cis-acting elements in the upstream region of the genes members of the family OsNramp subsp japonica cv. Nipponbare. A total of 14 elements were common to the eight members of the family OsNramp subsp japonica cv. Nipponbare. The element CACTFTPPCA1 was the most frequent motif in the promoter region of the genes of the family OsNramp of Oryza sativa subsp japonica cv. Nipponbare. The objective of the last work was to compare the sequences of oats with the species Arabidopsis, barley, rice, sugarcane, Sorghum, wheat and corn, looking for to infer evolutionary relationships of those species with the oats. Sequences of eight species of plants evaluable at the present moment, in the Unigene data bank in the National Center for Biotechnology Information - NCBI were downloaded and comparisons with oat made using the BLASTn and tBLASTx tools. It was observed that the bank of ESTs of oats UNIGENE-NCBI consists from many sequences a little similar to other species compared to nucleotides (46,72%) and aminoacids (74,97%). Only 4,56% of the sequences present in the UNIGENE-NCBI oat EST bank presents high similarity with sequences of mono and dicotyledonous species.